Theory of Mind, Personal Epistemology, and Science Learning: Exploring Common Conceptual Components - Kyriakopoulou, Natassa; Vosniadou, Stella (Frontiers in Psychology, 2020)
We investigated the hypothesis that theory of mind (ToM) and epistemological understanding promote the aspect of science learning that concerns the ability to understand that there can be more than one representation of the same phenomenon in the physical world. Sixty-three students ranging in age from 10 to 12 years were administered two false belief ToM tasks, an epistemological understanding task that investigated beliefs about the nature of science, and a science learning task. The science learning task required distinguishing and reflecting upon phenomenal and scientific depictions of phenomena in observational astronomy. A three-stage hierarchical multiple regression showed that ToM was a significant predictor of performance in the astronomy task supporting the hypothesis of a common underlying conceptual component. The results also showed that performance in the personal epistemology - nature of science task was a significant predictor of performance in the astronomy task, even when ToM and age were taken into consideration. The results indicate that both ToM and epistemological understanding promote the ability to construct and reflect on phenomenal and scientific representations of the same situation in the physical world and have important implications for science education.